Weight Management Experience of Women Living with Obesity: A Qualitative Study - Sri Dewi (CV. CENDIKIA JENIUS INDONESIA, 2025)
Background : Obese women are expected to have physical and psychosocial problems and need to modify their lifestyles. This study explored the factors that influenced weight management failure based on the experience of obese women in West Sumatra with Minangkabau culture. Methods: Six-Focus Group Discussions were conducted with thirty-one women living with obesity, selected by purposive sampling. A qualitative descriptive study design was used and analyzed using qualitative content analysis Results: Eight main themes emerged: difficulty moving and irregular periods as physical problems related to obesity; facing ostracization and psychological complaints due to obesity; restricting food intake but struggling with digestive complaints.; unable to avoid unhealthy food and eating in social settings; restricted outdoor activities due to other people's thoughts and judgments; barriers to participating in sports; family and environment support; and the desire that has not been fulfilled. Conclusion: The results of this study indicate the existence of sociocultural influences for obese women in weight management programs. There is a need for culturally sensitive interventions to improve the role of community leaders and the social environment for women with obesity.